CBIO-20. MOLECULAR MECHANISMS OF OLIG2 TRANSCRIPTION FACTOR IN GLIOBLASTOMA. (9th November 2020) - Saito, Norihiko; Sato, Sho; Hiramoto, Yu; Fujita, Satoshi; Nakayama, Haruo; Hayashi, Morito; Ito, Keisuke; Sakurai, Takatoshi; Iwabuchi, Satoshi
Abstract: Oligodendrocyte lineage transcription factor 2 (OLIG2) promotes proliferation of normal neural stem/progenitor cells and glioma cells. However, the mechanisms underlying the regulation of OLIG2 remain largely unknown. Here, we show that a comprehensive analysis of the critical gene regulatory networks involving OLIG2 in glioma initiating cell (GIC) lines. In vitro differentiation studies showed that proneural GIC lines possess the potential to differentiate into astrocytic, neuronal, and oligodendrocytic lineages, whereas mesenchymal GICs exhibited limited potential for neural lineage differentiation following retinoic acid induction. We also showed that CDK2-mediated OLIG2 phosphorylation stabilizes OLIG2 protein from proteasomal degradation. Phosphorylated OLIG2 binds to the E-Box regions of p27 promoter and represses p27 transcription, which in turn activates CDK2 in positive feedback manner. CDK2-mediated OLIG2 phosphorylation promotes cell cycle progression, cell proliferation, and tumorigenesis. OLIG2 inhibition disrupted cell cycle control mechanism by decreasing CDK2 and elevating apoptosis-related molecules. Inhibition of CDK2 activity disrupted OLIG2-CDK2 interactions and attenuated OLIG2 protein stability.　In addition, OLIG2-high glioma initiating cells are highly sensitive to CDK2 inhibitor treatment, indicating that OLIG2 can be a biomarker for personalized treatment for glioblastoma patients with CDK2 inhibitors. In conclusion, we have identified OLIG2-CDK2 interactions in glioma stem cells that can be targeted by CDK2 inhibitors and this may allow the selection of patients with high likelihood of responding to this therapy.